\(\Leftrightarrow-\frac{1}{6}< -\frac{1}{3}x+2< \frac{1}{6}\)
\(\Leftrightarrow\hept{\begin{cases}-\frac{1}{3}x+2>-\frac{1}{6}\\-\frac{1}{3}x+2< \frac{1}{6}\end{cases}\Leftrightarrow}\hept{\begin{cases}x< \frac{13}{2}\\x>\frac{11}{2}\end{cases}\Leftrightarrow\frac{11}{2}< x< \frac{13}{2}}\)
vậy
Xét 2 Th nha :
Th1 : \(\left|-\frac{1}{3}x+2\right|< 0\)
PT trở thành : \(\frac{1}{3}x-2< \frac{1}{6}\)
\(\Rightarrow\frac{1}{3}x< \frac{13}{6}\)
\(\Rightarrow x< \frac{13}{2}\)
Th2 : \(\left|-\frac{1}{3}x+2\right|\ge0\)
\(\Rightarrow\frac{-1}{3}x+2< \frac{1}{6}\)
\(\Rightarrow\frac{-1}{3}x< \frac{-11}{6}\)
\(\Rightarrow x>\frac{11}{2}\)
Tự kết luận nha . Nhớ xét điều kiện nha
\(\left|-\frac{1}{3}x+2\right|\)luôn dương mà